2013
DOI: 10.1371/journal.pone.0051174
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Intrinsic and Extrinsic Bounded Noises in Biomolecular Networks

Abstract: After being considered as a nuisance to be filtered out, it became recently clear that biochemical noise plays a complex role, often fully functional, for a biomolecular network. The influence of intrinsic and extrinsic noises on biomolecular networks has intensively been investigated in last ten years, though contributions on the co-presence of both are sparse. Extrinsic noise is usually modeled as an unbounded white or colored gaussian stochastic process, even though realistic stochastic perturbations are cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 82 publications
(159 reference statements)
0
42
0
Order By: Relevance
“…In this study we have focused on intrinsic noise. Several studies have looked at the effect of feedback systems on extrinsic noise (Shahrezaei and Swain, 2008a;de Franciscis et al, 2016;Caravagna et al, 2013;Assaf et al, 2013). In particular, it has been shown that negative feedback is effective in reducing extrinsic noise as well as intrinsic noise.…”
mentioning
confidence: 99%
“…In this study we have focused on intrinsic noise. Several studies have looked at the effect of feedback systems on extrinsic noise (Shahrezaei and Swain, 2008a;de Franciscis et al, 2016;Caravagna et al, 2013;Assaf et al, 2013). In particular, it has been shown that negative feedback is effective in reducing extrinsic noise as well as intrinsic noise.…”
mentioning
confidence: 99%
“…To be realistic, since bacteria’s volume and eukaryotic cellular nucleus oscillate in the volumetric range of 10:10 3   μm 3 , we explore values in  7677. Moreover, to efficiently calculate phase diagrams for this model we approximated an exact algorithm by observing that the network and noise time-scales are very well separated61. To check the consistency of this approximation, the probability density of protein counts is double-checked with the one predicted by the exact algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…This exact network representation can be simulated efficiently only when a few hundreds of proteins are present and the time-scales of the involved events are homogenous; if this is this case, an exact algorithm can be used2561. If one sets noise intensity to B  = 0, then this process becomes time-homogeneous86.…”
Section: Methodsmentioning
confidence: 99%
“…In particular it would be important to assess how the stochasticity of the gene switching interplays with extrinsic disturbances, such as (i) periodic fluctuations as those induced by circadian rhythms, which have the potential of deeply affecting the pharmacodynamics of cytotoxic and cytostatic drugs [41], or those induced by shorter rhythms caused by intracellular periodic variations of interfering TFs. In the latter case, it might be intriguing the case where these rhythms have a period similar to the average gene switching time, because of the possible onset of resonance effects; and (ii) fully random extrinsic perturbations [42] to be modelled by means of appropriate bounded stochastic processes [42,43]. In particular, it would be of relevance to investigate the case in which these perturbations affect the threshold Th.…”
Section: Discussionmentioning
confidence: 99%